Students online purchasing behavior in Malaysia: understanding online shopping attitude - Zendehdel, Marzieh; Paim, Laily; Osman, Syuhaily (Cogent OA, 2015)
Studies examining the factors that affect the online purchasing behavior of consumers are rare, despite the prospective advance of e-commerce in Malaysia. The present study examines particular factors that influence the attitude of potential consumers to purchase online by using the attributes from the diffusion of innovations theory of Rogers, the attribute of perception of risk, and the subjective norms toward online purchasing. Consumers’ perceived risks of online shopping have become a vital subject in research because they directly influence users’ attitude toward online purchasing. The structural equation modeling method was used to analyze the data gathered on students using e-commerce, and, thus, to validate the model. According to the results, consumers’ attitude toward online purchasing affects the intention toward online purchasing. The other influential factors are compatibility, relative advantage, and subjective norm.